The broadband light analyzer of complex aerosol: characterization and first applications - Tommaso Isolabella; Marco Brunoldi; Federico Mazzei; Franco Parodi; Paolo Prati; Virginia Vernocchi; Vera Bernardoni; Gianluigi Valli; Roberta Vecchi; Paola Formenti; Clarissa Baldo; Mathieu Cazaunau; et al. (Atmospheric Environment, 2025)

Does Perceived Nuisance Abundance of Water Plants Match with Willingness-to-Pay for Removal? Contrasts Among Different User Categories - Jan E. Vermaat; Kirstine Thiemer; Bart Immerzeel; Susanne C. Schneider; Keneilwe Sebola; Julie Coetzee; Antonella Petruzzella; Samuel N. Motitsoe; Mathieu Baldo; Benjamin Misteli; Gabrielle Thiébaut; Sabine Hilt; et al. (Environmental Management, 2025)
Dense beds of water plants can be perceived as nuisance, but this perception, however, may not be similar for different user categories, and this may affect their willingness-to-pay (WTP) for plant removal. A questionnaire survey was used to test this for residents and visitors and find underlying socio-cultural or economic drivers. We studied five cases where nuisance water plant growth is managed: the rivers Otra (Norway) and Spree (Germany), and the lakes Kemnade (Germany), Grand-Lieu (France), and Hartbeespoort Dam (South Africa). We used a different payment vehicle for residents (annual household tax) and visitors (tourist tax). The survey included questions on days spent on specific types of activity per year, the importance attached to different functions and activities, overall environmental attitude, perception of the plants, socio-demographic respondent characteristics and WTP for increased plant removal. We observed no increase in WTP for increased removal in most sites. The two most important drivers of variation in current WTP were income, and whether respondents were engaged in boating and angling and thus perceived the plants negatively. Variation in WTP among sites was considerable, and mainly related to the mixture of activities among respondents. Differences between residents and visitors were less important than those among sites. Our observations bear importance for water management: information on differences in experienced nuisance among user categories and the frequency of use by these categories is useful as guidance for the design and implementation of any plant removal plan.

Drivers of Perceived Nuisance Growth by Aquatic Plants - Kirstine Thiemer; Bart Immerzeel; Susanne Schneider; Keneilwe Sebola; Julie Coetzee; Mathieu Baldo; Gabrielle Thiebaut; Sabine Hilt; Jan Köhler; Sarah Faye Harpenslager; Jan E. Vermaat (Environmental Management, 2023)
Mass developments of macrophytes occur frequently worldwide and are often considered a nuisance when interfering with human activities. It is crucial to understand the drivers of this perception if we are to develop effective management strategies for ecosystems with macrophyte mass developments. Using a comprehensive survey spanning five sites with different macrophyte species in four countries (Norway, France, Germany and South Africa), we quantified the perception of macrophyte growth as a nuisance among residents and visitors, and for different recreational activities (swimming, boating, angling, appreciation of biodiversity, appreciation of landscape and birdwatching). We then used a Bayesian network approach to integrate the perception of nuisance with the consequences of plant removal. From the 1234 responses collected from the five sites, a range of 73–93% of the respondents across the sites considered macrophyte growth a nuisance at each site. Residents perceived macrophytes up to 23% more problematic than visitors. Environmental mindedness of respondents did not influence the perception of nuisance. Perceived nuisance of macrophytes was relatively similar for different recreational activities that were possible in each case study site, although we found some site-specific variation. Finally, we illustrate how Bayesian networks can be used to choose the best management option by balancing people’s perception of macrophyte growth with the potential consequences of macrophyte removal.